Studies on Antitumor Substances. XII. Synthesis of Bis (2, 3-epoxypropyl) amine Derivatives and the Reaction with Some Nucleophiles - FUJINO, YOKO; FURUKAWA, MITSURU; NAKAO, TORU; SUGITA, MAKOTO; HAYASHI, SEIGORO (Chemical & pharmaceutical bulletin, 1971)
Several bis (2, 3-epoxypropyl) amine derivatives were successfully synthesized by the modification of Homer's method. N, N'-Bis (2, 3-epoxypropyl) piperazine and p-bis (2, 3-epoxypropoxy) benzene were attempted to react with thiols, amines and phenol, and the corresponding ring opening compounds of the epoxide ring were obtained in good yields, respectively. N, N'-Bis (2, 3-epoxypropyl) piperazine and p-bis (2, 3-epoxypropoxy) benzene also reacted with diethyl malonate to give N, N'-bis (γ-ethoxycarbonyl-γ-butyrolacton-α-yl) methyl piperazine and p-bis (γ-ethoxycarbonyl-γ-butyrolacton-α-yl) methoxy benzene, respectively.